SMART PARENTING: UPAYA PENINGKATAN KEMAMPUAN KOGNITIF DAN KREATIVITAS ANAK DI KELURAHAN BANJARJO, BOJA, KENDAL - Astuti, Henny Puji (Universitas Negeri Semarang, 2014)
Smart parenting is intelligent parenting by parent and adults in order satisfy needs, provide protection and educate in daily life in achieving development optimal. Children’s problems are caused by mistakes or ignorance of parents going the way of communication and the delivery of the right method in children. For most parents conscious and unconscious; often treat children as a robot that can be instructed and have to run any commands that given to him. They forgot that a child is also a individuals in the smaller having, feeling, desires, and action.Training about smart parenting is addressed in the parents in the county of Kendal, especially the mothers who become the object of attaching first child. Devotion to this community will discuss about optimization cognitive development and creativity early childhood. Expectation of this training is parent to have knowledge and understanding new in apply to a child, talking about parenting especially for improvement of cognitive and creativity child. The parents expected to child care with good and right, accompanying in passing duty child development, and created a generation of gold for the future.